High Performance Flexible Tribo/Piezoelectric Nanogenerators based on BaTiO3/Chitosan Composites. Issue 1 (29th December 2021) - Pongampai, Satana; Charoonsuk, Thitirat; Pinpru, Nattapong; Muanghlua, Rangson; Vittayakorn, Wanwilai; Vittayakorn, Naratip
Abstract: Natural biopolymer materials have been of interest in wearable energy harvester technology, especially in biocompatible triboelectric nanogenerators (BTENGs), due to their biodegradable, biocompatible, nontoxic and excellent antibacterial properties. Nevertheless, obstacles concerning economical and biocompatible utilization of triboelectric nanogenerators (TENGs) continue to prevail. The natural biopolymer, chitosan (CS), is composed of a long biopolymer chain of N-acetyl glucosamine. It enables exciting opportunities for low-cost, biodegradable triboelectric nanogenerator (TENG) applications. However, the electrical output performance of CS based on TENGs is low when compared with devices constructed from synthetic polymers. Hence, to enhance electrical output performance, BaTiO3 nano-powders (BT-NPs) were embedded into the CS as dielectric material, in order to improve electrical properties by increasing the dielectric constant of the composite film. A flexible hybrid piezo/triboelectric nanogenerator, designed by BT-NPs embedded into CS (BT-NPs/CS) composite film, was constructed successfully. The effects of the BaTiO3 nano-powder (BT-NP) content on the output performance were explored systematically. The device with 5 wt% BT-NPs in CS, and a 160-μm-thick film, exhibited maximum open-circuit voltage (VOC ) and transferred short-circuit current (ISC ) of 110.8 V and 10 µA, respectively, as well as maximum power output of 431.8 µW. Practical and application demonstrations also were investigated, namely charged capacitors for storing energy, testing voltage stability and driving commercial LEDs. This work exhibited high electrical performance enhancement of BT-NPs/CS nanocomposite film, which demonstrated better material modification. Graphical Abstract: UF0001